Nem injeção e nem xabori : reflexão sobre trabalhos de saúde mental em contextos indígenas de Roraima - Vieira, Edilaise Santos (2018)
Following indigenous peoples’ mobilizations and the creation of the Indigenous Mental Health Care Policy (Ministry of Health decree nº 2.759 of 2007) the developments of psychosocial care for indigenous populations in Brazil are the object of thought and debate. In the State of Roraima these actions are being carried out by Special Indigenous Health Districts (SIHD), East and Yanomami, reflected in the Indigenous Mental Health Programme and its articulation with the State Psycho-Social Care Network. This research aims to know actors involved and describe their practices carried out in mental health care within the indigenous context, through their own experiences’ narratives. The work is divided in four chapters: in the first one I express my own self-narrative, by exposing my living experience as an indigenous psychologist in action on the theme; in the second one, I seek to analyse the approach of psychology to indigenous issues, which has become a reference in dealing with mental health issues, and introduce the psychology professionals working in the East and Yanomamy districts; in the third one I explain the mental health policy for indigenous peoples and, through the narratives of those involved, I point out the negotiations’ hallenges in implementing the mental health policy in this State; finally, in the fourth chapter I discuss the Indigenous Well Living as something legitimate to recognise and value the “indigenous way of being”.